1999
DOI: 10.1891/0886-6708.14.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Men’s Subtle and Overt Psychological Abuse on Low-Income Women

Abstract: Asocial influence approach to the psychological abuse of women (Marshall, 1994; 1996) was expanded and tested. Distinctions are made between obvious acts (e.g., verbal aggression, controlling behaviors), overt acts which are easily recognized and described, and subtle acts which are least likely to be recognized as psychologically abusive. Men’s violence and sexual aggression, and overt (dominating acts, indifference, monitoring, discrediting) and subtle (undermining, discounting, isolating) psychological abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
115
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 0 publications
11
115
1
6
Order By: Relevance
“…Mothers and fathers also completed the Subtle and Overt Psychological Abuse of Women and Men Scale (SOPAS; Marshall, 2001), a 35-item scale that assesses psychological abuse. Participants rated how often their spouse had used a list of behaviors in either a loving, joking, or serious manner on a scale ranging from 0 (never) to 6 (a great many times).…”
Section: Methodsmentioning
confidence: 99%
“…Mothers and fathers also completed the Subtle and Overt Psychological Abuse of Women and Men Scale (SOPAS; Marshall, 2001), a 35-item scale that assesses psychological abuse. Participants rated how often their spouse had used a list of behaviors in either a loving, joking, or serious manner on a scale ranging from 0 (never) to 6 (a great many times).…”
Section: Methodsmentioning
confidence: 99%
“…There is also a link to the category of control established by Vázquez et al, (2008), to that of external control proposed by , to Ward's environment control (2000), and to the category of isolation control activity suggested by Wolfson (2002). The category of isolation finds its counterpart in the isolating category put forward by Jones et al (2005) and Marshall (1999), as well as in the description of isolation proposed by Sonkin, Martin and Walker (1985) and Vázquez et al (2008), in Kasian and Painter's isolation and control (1992), in Tolman's domination/isolation (1989), and in Walker's social isolation (1979). The strategy of imposing one's own thinking has been less widely considered by other researchers and their classifications cover less ground than the category proposed here.…”
Section: Discussionmentioning
confidence: 98%
“…The categories covering the control and manipulation of information and control of personal life bear a certain connection to those overt actions (Marshall, 1999) whose aim is to supervise the behaviour of women, as well as to the abuse of control exercised by the abuser over his victim, a category reflected in the work of Pitzner and Drummond (1997). There is also a link to the category of control established by Vázquez et al, (2008), to that of external control proposed by , to Ward's environment control (2000), and to the category of isolation control activity suggested by Wolfson (2002).…”
Section: Discussionmentioning
confidence: 99%
“…All definitions of psychological abuse incorporate at least one form of negative verbal messaging directed at a partner. Victims of psychological abuse are commonly criticized (Marshall, 2001;0' Leary & Jouriles, 1994), called names, intentionally made to feel inadequate (Marshall, 2001;Outlaw, 2009), have their abilities undermined (Marshall, 2001), and are deliberately humiliated or diminished (O'Leary & Jouriles, 1994;Saltzman et aI., 2002) by an intimate partner. Bandura (1997) also includes indirect or subtle messages of efficacy in his definition of verbal persuasion, as they are often equally clear forms of communication.…”
Section: Psychological Abuse and Self-efficacy Erosionmentioning
confidence: 99%
“…Additional studies have reported similar results Gist, Schwoerer, & Rosen, 1989;Williams, 1982) Social isolation, as an aspect of psychological abuse, limits one's personal territory or freedom by restricting access to friends or family and/or preventing a person from working, going to school, or doing things independently (Maiuro, 2001). Social isolation is included as a core component in multiple conceptual frameworks of psychological abuse (Maiuro, 2001;Marshall, 2001;NiCarthy, 1986;Hoffman, 1984;Russell, 1982;Sonkin, Martin, & Walker, 1985), is assessed by validated measures of IPV (Hegarty, Sheehan, & Schonfeld, 1999;Hudson & McIntosh, 1981;Tolman, 1989Tolman, , 1998, and occurs cross-culturally (Garcia-Moreno, Jansen, Ellsberg, Heise, & Watts,…”
Section: Psychological Abuse and Self-efficacy Erosionmentioning
confidence: 99%